A topology identification algorithm and device implementation based on smart switch core board. Issue 1 (1st March 2022) - Huo, Chao; Wang, Yutuo; Mu, Di
Abstract: Due to the large scale, large number of equipment and complex structure of distribution network, relying on manual maintenance of distribution network topology model has a huge workload and poor intuitiveness of model information, which is difficult to ensure the integrity and correctness of distribution network topology model. This paper presents an algorithm to improve the adaptability of multi scene feature signal recognition based on the smart switch core board, and designs the local communication interaction flow design based on topology recognition function from the station area intelligent terminal to the smart switch. The identification technology combining power frequency distortion and characteristic current is adopted. In the identification process, there is no need for the master station to participate in analysis and control. Multiple stations in the same community can be carried out concurrently to automatically identify the connection relationship between distribution network equipment and line topology, and dynamically build a clear and complete household transformer relationship and distribution network topology to help operation inspection, marketing The lean management level of distribution network such as regulation and control has been improved.